Pengaruh Komunikasi dan Kemampuan Sumber Daya Manusia terhadap Efektivitas Kerja Pegawai - Mulyani, Sri; Murni, Yanti; Putri, Maharani; Afrianti, Rini (SAFE-Network, 2023)
The aim of this research is to realize Quality and Accountability of Government Services in the District. The data source used in this research is primary data. This research was conducted at the South Pariaman District Head Office, Pariaman City, located on Jl. Zaini No.1, Balai Kurai Taji, Pariaman Sel., Pariaman City, West Sumatra 25536, Indonesia. The research will be carried out in June 2022 until completion. Based on the research results, it was concluded that communication had a significant effect on employee work effectiveness at the South Pariaman District Head Office, Pariaman City with a significance level of 0.000 < 0.05; Human Resource Capabilities have a significant effect on Employee Work Effectiveness at the South Pariaman Subdistrict Office, Pariaman City with a significance level of 0.001 < 0.05; and Communication and Human Resource Capabilities have a significant effect on Employee Work Effectiveness at the South Pariaman Subdistrict Office, Pariaman City with a significance level of 0.000 < 0.05;. The R Square value was obtained at 0.984, this means 98.4%, which means that the ability of the Communication (X1) and Human Resources Ability (X2) variables in explaining the Work Effectiveness variable (Y) is 98.4%. Meanwhile, the remainder (100% - 98.4%= 1.6%) is explained by other variables outside of this research variable.